Patterns of WH-Question in English used by EFL Students - Gitit I.P Wacana (Sintuwu Maroso Journal of English Teaching, 2016)
The aims of this research are: (1) To describe how the teacher teach the students about WH question, and; (2) To find out how far the students have competence to product WH question in English at the SMPN Satu Atap Uelincu. This research was a qualitative. Data were collected from observation and interview. The sources of data were students and English teacher. The findings show that EFL students at the SMP Negeri Satu Atap Uelincu have a good competence to use the pattern of WH question in English.Keywords: patterns, WH questions